CREATING E-LOYALTY ON ONLINE SHOPPING TRANSACTION THROUGH E-SERVICE QUALITY AND E-TRUST - Muh. Feroza A.; M Muhdiyanto; Diesyana Ajeng Pramesti (Muhammadiyah International Journal of Economics and Business, 2018)
The objective of this research is to determine the extent of e-service quality and e-trust influence thee-loyalty in online shopping by combining two research models. This research employs survey by usingpurposive sampling technique to 120 internet users in Magelang, Central Java. The respondents of the research are customer that ever doing transaction more than 2 times in the website. The data analysis was done using SPSS 21.00 and hypothesis testing was through Path Analysis. The research identifiesthat four hypotheses are supported that are the relationship between of e-service quality, e-trust toe-satisfaction and e-satisfaction, e-trust to e-loyalty are positive and significant and one hypothesis isnot supported that is the relationship between e-service quality to e-loyalty is positive but not significant.